IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA (SDM): STUDI EMPIRIK DI KANTOR KONSULTAN LARISPA - Muhammad Rizal; Aris Darya Fernanda (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
This study aims to investigate the implementation of human resource management in a consultant and research institution, Larispa which is located in Medan. The study used a qualitative approach with interviews, observation and analysis of documents as instruments in data collection. Interviews were conducted with someone who is considered as a key person and knows many things about the company. Observations was carried out directly in the location to see the phenomena that takes place without disrupting the company's activities, as well as document analysis so that all the data would then be analyzed and cross-checked with each other. The results showed that Larispa implemented management strategies well including work appraisal management, involvement of employees in taking decisions, intensive giving and compensation, work protection, occupational health and safety, building communication between employees, enforcing strict discipline or regulations for employees, giving administrative sanctions and work terminations for employees who break the rules. Furthermore, Larispa was impressed defender, which was concentrating on the current market, protecting and maintaining stable growth and serving its customers with the best services. Larispa also considered not having other competitors, thus strengthening the defender strategy to continue and survive as it was comfortable in the position with particular marketing without any challenges and competitions.